An Overview Of Augered, Cast In Place Piles In Florida - Introduction - Kirk A. Mcintosh (Deep Foundations Institute, 1997)
Augered, cast-in-place (ACIP) piles have been utilized in the United States for a wide range of projects since the 1950's. Due to the cast-in-place nature of the installation method (and lack of a driving criteria); however, ACIP piles have not been readily accepted by some practicing geotechnical and structural engineers. Since ACIP piles were initially developed, the installation equipment and techniques have been improved and refined and the number of experienced contractors has significantly increased. Over the past 10 to 15 years, the pile type has experienced significant growth in the United States (particularly in Florida) because engineers have become more knowledgeable and comfortable with its use. The Miami area, in particular, has experienced considerable growth in the utilization of ACIP piles primarily due to their usage on the $1 billion Miami Metrorail System project in the early 1980s. The economic advantages over other deep foundation types, coupled with some unique installation advantages, have shown that ACIP piles can be a viable foundation alternative on many projects. Even though ACIP piles have gained respect in the private sector, the pile type has generally not been readily accepted by government transportation agencies. The reluctance to readily accept this foundation type stems primarily from the quality assurance aspect of cast-in-place pile construction. Additionally, there has not been much research activity on this foundation type, technical papers, formal associations (other than the DFI), or a concerted effort to standardize the industry. This paper serves to discuss the state of practice for ACIP pile installation in the state of Florida.